Cover Feature: Multi‐Valent Group 14 Chalcogenide Architectures from Ionic Liquids: 0D‐[Cs@SnII4(GeIV4Se10)4]7− and 2D‐[SnII(GeIV4Se10)]2− (Chem. Eur. J. 46/2018). Issue 46 (19th July 2018) - Santner, Silke; Wolff, Alexander; Ruck, Michael; Dehnen, Stefanie
Abstract : A unique supertetrahedral anion embedding a Cs + cation is found in (C4 C1 C1 im)7 [Cs@Sn II 4 (Ge4 Se10 )4 ], obtained upon ionothermal reaction of Cs4 [Ge4 Se10 ]⋅H2 O and SnCl4 ⋅5H2 O with [Pt@Bi10 ][AlBr4 ]4 as reducing agent. The anion's topology is related to that of P2 supertetrahedral clusters, yet the T2‐type supertetrahedral [Ge4 Se10 ] units are not linked via an inverse T2 unit, but via four Sn II atoms. These allow for capturing of the Cs + cation through their lone pairs. Quantum chemical studies show that the cavity in 1 is perfectly suited to accommodate a Cs + ion. More information can be found in the Communication by S. Dehnen, et al. on page 11899 .